The genus Alcochera Förster (Hymenoptera, Ichneumonidae, Ctenopelmatinae) in China with a key to world species - Sun, Shu-Ping; Li, Tao; Zong, Shi-Xiang; Sheng, Mao-Ling (Zootaxa, 2021)
Two new species of Alcochera (Ichneumonidae, Ctenopelmatinae, Mesoleiini), Alcochera flavoclypeata Sheng & Sun, sp. nov. collected from Labagoumen Natural Reserve, Huairou, Beijing, and A. truncata Sheng & Sun, sp. nov. from Wugongshan Natural Reserve, are described and illustrated. An updated taxonomic key to world species of Alcochera is provided.